PELAKSANAAN TUGAS GURU SEKOLAH DASAR NEGERI KECAMATAN ENAM LINGKUNG KABUPATEN PADANG PARIAMAN - Sri Ayuni Putri (Universitas Negeri Padang, 2013)
The goal of this research are to get information about implementation the task of teachers. The population is one hundred and eighty two teachers. And the sample is one hundred five teachers, that taken by stratified proportional random sampling. The instrument of this research is question with Likert scale models that had tested for validity and reliability. Data analyzed using mean score . The result of this research are the implementation the task of teachers in Public Elementry School Enam Lingkung Sub-district Padang Pariaman Regency stay is Good Enough. Keywords:The task of teachers